The Effects of Perceived Usefulness, Ease of Use, and Social Influence on The Decision to Use Online Loans Among Market Vendors in Klungkung District - Kadek Wahyu Pujangga; Gregorius Paulus Tahu; Ni Made Indah Mentari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, and social influence on the decision to use online loans by merchants at Klungkung District Market. The research method used a quantitative approach with a sample of 97 market merchants selected through purposive sampling. Data were collected via a questionnaire using a 1–5 Likert scale and analyzed using multiple linear regression. The results indicate that all three independent variables significantly influence the decision to use online loans. Perceived usefulness had the most dominant influence (β = 0.456; p < 0.001), followed by ease of use (β = 0.328; p < 0.001) and social influence (β = 0.287; p = 0.001). The regression model explains 68.7% of the variation in usage decisions. These findings provide practical implications for online loan service providers to enhance perceptions of benefits and ease of access, as well as to build community support to increase service adoption.